If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -8 = -3(-2x + 4) Reorder the terms: -8 + 6x = -3(-2x + 4) Reorder the terms: -8 + 6x = -3(4 + -2x) -8 + 6x = (4 * -3 + -2x * -3) -8 + 6x = (-12 + 6x) Add '-6x' to each side of the equation. -8 + 6x + -6x = -12 + 6x + -6x Combine like terms: 6x + -6x = 0 -8 + 0 = -12 + 6x + -6x -8 = -12 + 6x + -6x Combine like terms: 6x + -6x = 0 -8 = -12 + 0 -8 = -12 Solving -8 = -12 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 1=13x-2 | | O(15)=2n-1 | | 2/3/3/4=x/1/5 | | (n+1)(9n+8)=0 | | 11x-x=42 | | (8x-18)+(x)=90 | | 2/3.3/4=5X | | (q+8)(4q-5)=0 | | 2r^2+8r-3=-11 | | -u+63=249 | | 3x-3(-6)=9 | | 8r^2+8r-3=-11 | | 222=10-y | | 3x-3(0)=9 | | 0=93.5-78x+15x^2 | | 104=170-v | | (13x-2)+(x)=90 | | x*y=575000 | | 4v-7=-19 | | Y=0.3x+35 | | 7/3=6/x | | 0=1-2x+4x^2 | | 2826=2r*3.14 | | X-78=1/3×x-82 | | -6=m/5-3 | | 3(x+1)-2x=5-3x | | (4xb)-8=8 | | 2(t+7)=48 | | 9+3r-1=8r+16-3r | | 7n-1=169 | | 16x^2-2x-8=21 | | 3/7(x-8)=-3 |